Sustaining Occupational Information for Career Choice and Development in Students of Technical Colleges in Enugu State, Nigeria - Odo, Moses Ikebe (Journal of Technical Education and Training, 2015)
This study takes on the issue of sustaining occupational information for career choice and development in students of technical colleges in Enugu State, Nigeria. The method adopted for this study was the survey design and the population included were all final year students of the three government technical colleges in Enugu State of Nigeria. The technical colleges were sampled as follows: Government Technical College, Enugu (156 students); Government Technical College, Nsukka (148 students); and Government Technical College, Akpugoeze (132 students). Four research questions were raised for the study. A total of 32 structured questionnaire were developed to elicit information from the respondents. The data gathered were analysed using mean and standard deviation. The findings of the study revealed that occupational information helps students make better career choice through exposure and knowledge gained on world of work. Environment, personality of the students, qualities of occupation and opportunities available, influence career choice of technical college students. The career resource library, programmes, seminars, workshops and vocational college counsellor are sources of career information. It is recommended that students should find sources on career information especially from online and vocational college counsellors before making any career choice or occupations to match their personalities and abilities